The Role of MARPOL in Promoting a Transdiciplinary to Pollution Management in Ports - Chairunnisa, Andi Sitti (Collaborate Engineering Daily Book Series, 2024)
This study examines the impact of MARPOL regulations on pollution management in port environments, emphasizing the importance of a transdisciplinary approach. Through case studies of the Port of Rotterdam, the Port of Singapore, and the Port of Los Angeles, the research reveals that compliance with MARPOL significantly reduces oil pollution and wastewater discharge, demonstrating the effectiveness of these international maritime regulations. The findings highlight the critical role of stakeholder collaboration, involving port authorities, shipping companies, environmental NGOs, and local communities, in achieving high compliance rates and fostering a culture of shared responsibility. However, challenges such as financial constraints for smaller shipping companies and the complexities of international maritime regulations can hinder compliance efforts. To address these challenges, the study advocates for targeted financial incentives, enhanced training programs, and the establishment of formal partnerships among stakeholders. By promoting cooperation and knowledge sharing, ports can leverage collective expertise to improve environmental performance continuously. Overall, the insights gained from this research not only contribute to understanding MARPOL's influence on pollution management but also provide valuable recommendations for advancing sustainability in port operations, ultimately supporting the protection of marine ecosystems and the maritime sector's sustainable future.